1993
DOI: 10.1016/0014-5793(93)81540-g
|View full text |Cite
|
Sign up to set email alerts
|

P‐glycoprotein‐mediated transcellular transport of MDR‐reversing agents

Abstract: Understanding of the interactions between P‐glycoprotein and multidrug resistance (MDR) reversing agents is important in designing more effective MDR modulators. We examined transcellular transport of several MDR modulators by using a drug‐sensitive epithelial cell line, LLC‐PK1 and its transformant cell line, LLC‐GA5‐COL300, which expresses human P‐glycoprotein on the apical surface. Basal‐to‐apical transports of azidopine and diltiazem across the LLC‐GA5‐COL300 monolayer were increased and apical‐to‐basal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
2
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 15 publications
3
75
2
1
Order By: Relevance
“…Therefore, ticlopidine might possible increase absorption of carvedilol in the intestine through the inhibition of CYP2C9. In addition to its extensive metabolism by CYP2C9, carvedilol appeared to be the substrate of P-gp, suggesting that P-gp and CYP2C9 should act synergistically to limit the oral bioavailability of carvedilol (Saeki et al, 1993). Therefore, we investigated the cell-based P-gp activity using rhodamne-123 and the result showed that ticlopidine did not affect P-gp activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ticlopidine might possible increase absorption of carvedilol in the intestine through the inhibition of CYP2C9. In addition to its extensive metabolism by CYP2C9, carvedilol appeared to be the substrate of P-gp, suggesting that P-gp and CYP2C9 should act synergistically to limit the oral bioavailability of carvedilol (Saeki et al, 1993). Therefore, we investigated the cell-based P-gp activity using rhodamne-123 and the result showed that ticlopidine did not affect P-gp activity.…”
Section: Discussionmentioning
confidence: 99%
“…These latter modulators compete for outward transport of the MDR-related drugs (e.g. cyclosporin A, FK-506, azidopine I-NAPS, and ivermectin) [94,116,170,171].…”
Section: Specific Inhibitorsmentioning
confidence: 99%
“…Substrates for the human MDRllPgp include peptides such as valinomycin [lo], gramicidin D [l 11, cyclosporin A [12], a tripeptide N-acetyl-leucyl-leucyl-norleucinal [13], and yeast afactor mating peptide [14]. During our search for peptide antibiotics which interact with human Pgp, we found that Saccharomyces cerevisiae expressing human MDRllPgp showed resistance to aureobasidin A, a new antifungal cyclic depsipeptide antibiotic produced by Aureobasidium pullulans R106 [15,16].…”
Section: Introductionmentioning
confidence: 99%